2006
DOI: 10.1097/01.mib.0000209790.21737.28
|View full text |Cite
|
Sign up to set email alerts
|

CC-Type chemokine receptor 5-Δ32 mutation protects against primary sclerosing cholangitis

Abstract: Because an intact CCR5 receptor is needed for internalization of specific pathogens and homing of memory T lymphocytes to the liver, we hypothesize that a deficient expression of this receptor resulting from the CCR5-Delta32 variant may protect against PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Overall, in some situations, there appear to be less harmful inflammation seen, examples of this include increased renal allograft survival; 99 lower incidence of RA, and in those with RA, fewer exacerbations; 100 less Kawasaki disease, 101 lower rates of severe coronary artery disease; 102 increased renal survival with IgA nephropathy 103 and in those with inflammatory bowel disease (IBD), less primary sclerosing cholangitis (PSC). 104 However, these data in the setting of IBD, conflict with those from another observational study which indicated that PSC was more severe in those heterozygotes for the delta 32 deletion. 105 Other observations include less inflammation and fibrosis in hepatitis C virus (HCV) and greater HCV clearance, 106 and lastly decreased cerebral malaria in mice.…”
Section: Theoretical Benefits Of Blocking Ccr5-anti-inflammatory Propcontrasting
confidence: 51%
“…Overall, in some situations, there appear to be less harmful inflammation seen, examples of this include increased renal allograft survival; 99 lower incidence of RA, and in those with RA, fewer exacerbations; 100 less Kawasaki disease, 101 lower rates of severe coronary artery disease; 102 increased renal survival with IgA nephropathy 103 and in those with inflammatory bowel disease (IBD), less primary sclerosing cholangitis (PSC). 104 However, these data in the setting of IBD, conflict with those from another observational study which indicated that PSC was more severe in those heterozygotes for the delta 32 deletion. 105 Other observations include less inflammation and fibrosis in hepatitis C virus (HCV) and greater HCV clearance, 106 and lastly decreased cerebral malaria in mice.…”
Section: Theoretical Benefits Of Blocking Ccr5-anti-inflammatory Propcontrasting
confidence: 51%
“…Three PSC patients had a PSC-AIH overlap syndrome. As noted in an earlier study [29], the male predominance in PSC (overall men to women ratio approximately 3:2) was especially pronounced in the subgroup with IBD (78.3% male). In the subgroup with PSC alone, the sex ratio was more balanced (55.6% male).…”
Section: Resultsmentioning
confidence: 58%
“…Unfortunately, most of the studies describing an influence of genetic alterations on PSC development are not reproducible. For instance a 32-bp deletion of the chemokine receptor 5 (CR5D32), which is frequently found in Northern European countries, results in a reduced receptor expression on T-cells; a recent study on a Belgian population showed a significant lower frequency of this mutation compared with healthy control subjects suggesting a protective effect [26]. However, this is in contrast to a previous study from Australia, which found a higher frequency of CR5D32 in PSC patients [27].…”
Section: Psc As a Genetic Diseasementioning
confidence: 88%
“…Atypical perinuclear-staining, antineutrophil cytoplasmic antibodies (p-ANCA) can be found in 60-93% of patients with PSC but also in patients with AIH, PBC or UC [34][35][36]. Terjung et al identified a 50-kDa nuclear envelope protein as target antigen in 92% of atypical p-ANCA and proposed the more accurate term ''peripheral antineutrophil nuclear antibodies" (p-ANNA) [37]; nevertheless it is still questionable, whether this target protein or p-ANNAs are -Association with HLA-haplotypes is only weak and not mandatory -Association with certain MHC-and non-MHC-alleles [23][24][25][26][27][28][29][30][31] -Studies on non-HLA polymorphisms are not reproducible or contradictory PSC as an autoimmune disease -Increased incidence of co-existing autoimmune diseases [20] -No response on immunosuppressive treatment -Presence of multiple autoantibodies [33] -Male predominance -Antibodies are not specific and do not correlate with clinical parameters PSC as inflammatory reaction on infectious agents -Co-expression of VAP-1 and MadCAM-1 in the gut and the liver of patients with PSC and IBD allows an enterohepatic lymphocyte circulation [41,42,44,45] -In PSC patients without IBD enterohepatic lymphocyte circulation is not a conclusive concept -In a rat model small intestinal bacterial overgrowth lead to biliary strictures and portal inflammation [48] -No evidence of sign. bacteraemia in UC [46] -Helicobacter species can be found in 24-75% of PSC livers [50,52] - [66,67] involved in pathogenesis.…”
Section: Psc As An Autoimmune Diseasementioning
confidence: 96%